Prevalence of thalassemia among patients attending to Ibn-Al-Baldi hospital in Baghdad city (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
"Thalassemias": are forms of inherited recessive blood disorder that originated in the Mediterranean region. In" thalassemia", the disease is caused by the excessive destruction or degradation of red blood cells due to formation of abnormal hemoglobin molecules, because of a defect through a genetic mutation or deletion. The aim of this study to assess distribution of “thalassemia’s" patients according to  age, sex, area and types of disease in Baghdad city. This study concluded that higher percentage of Intermediate (32.6%) among age groups (